PENGARUH KECERDASAN SOSIAL TERHADAP KEPEDULIAN SOSIAL IBU RUMAH TANGGA KAMPUNG MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Rio Isgendi; Daeng Ayub Natuna; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the level of social intelligence of housewives in Maredan Barat Village, Tualang District, Siak Regency, to know and to analyze the level of social care of housewives in Maredan Barat Village, Tualang District, Siak Regency, to determine the positive and significant effect of social intelligence on housewives' social care. Maredan Barat Village, Tualang District, Siak Regency. This research is a type of ex post facto research, a quantitative descriptive study of two variables to find the influence between variables, before looking for influence it is necessary to find a correlation first. The population in this study were 129 housewives in Maredan Barat Village, Tualang Siak District. The sampling method used was the Simple Random Sampling method. The size of the sample used the Slovin formula so that the number of samples in this study was 57 housewives. Collecting data obtained by the author using documentation techniques, observation and questionnaires (questionnaires). Based on the analysis of the demographic factor analysis of respondents, high social intelligence, seen from the demographic factors of the respondents, obtained high results of 4.00 and the resilience of social care obtained high results with a mean of 3.95. Based on the descriptive analysis of the social intelligence variable of 3.99 with a high interpretation and 4.08 social care with a very high interpretation. Obtained a significant and positive influence on the social intelligence variable (X) on Social Concern (Y) the housewife of Maredan Barat Village, Tualang District, Siak Regency, the big influence is 47.00% with moderate interpretation, because there is still 36.90% determined by other factors. who were not part of this study.Key Words: Social Intelligence, Housewife Social Care.